Strengthening Characteristics of Organizational Structures as An Effort To Improve Madrasah Employee Performance - Hartina, Hartina; Hariyadi, Ahmad; Tukiyo, Tukiyo; Romadhianti, Rona; Seena, Ismaeel (JURNAL AL-TANZIM, 2022)
This paper aims to analyze the characteristics of the organizational structure and the efforts of the head of the madrasa to improve employee performance at the Amanatul Ummah Pacet International Standard Madrasah. This type of research has used descriptive qualitative. For data collection techniques, researchers used observation, interviews, and documentation. The data analysis in this study begins before being in the field, analyzing data in the field, reducing data, presenting data, and drawing conclusions. The results showed that the characteristics of the organizational structure in the Amanatul Ummah Pacet International Standard Madrasah impacted employee performance. Characteristics of the organizational structure here using the line staff organizational structure are different from school institutions. The organizational structure at the Amanatul Ummah Pacet International Standard Madrasah impacts employee performance where the performance has a perfect communication pattern.